1996
DOI: 10.1177/002221949602900305
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal Reading: Benefits of a Talking Computer for Average and Less Skilled Readers

Abstract: Studies have shown that when information is presented through visual and auditory channels simultaneously (i.e., bimodal presentation), speed of processing and memory recall are enhanced. The present study demonstrated the efficacy of a bimodal approach to fostering reading comprehension. Eighteen average readers (9 girls and 9 boys) and 18 less skilled readers (8 girls and 10 boys) in Grades 8 and 9 participated in the study. Students were presented with social studies and science passages via a computer. Pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 33 publications
(38 reference statements)
4
64
0
2
Order By: Relevance
“…I have noticed, as Montali and Lewandowski (1996) did, that poor writers not only felt more successful with bimodal presentation, but were more successful in terms of comprehending content in this environment. Though the University has long introduced the use of computer and Internet into the traditional classroom teaching and learning of various courses, few empirical studies have been done to examine its effectiveness and impact, as what Beatty observed (2003) almost a decade ago.…”
Section: Focus Of the Present Studymentioning
confidence: 56%
See 1 more Smart Citation
“…I have noticed, as Montali and Lewandowski (1996) did, that poor writers not only felt more successful with bimodal presentation, but were more successful in terms of comprehending content in this environment. Though the University has long introduced the use of computer and Internet into the traditional classroom teaching and learning of various courses, few empirical studies have been done to examine its effectiveness and impact, as what Beatty observed (2003) almost a decade ago.…”
Section: Focus Of the Present Studymentioning
confidence: 56%
“…For example, Bush and Crotty (1991) compared videodisc instruction with traditional instruction and concluded that the use of videodisc exercises made practice inherently more meaningful than traditional text-based exercises. Montali and Lewandowski (1996) found that poor readers not only felt more successful with bimodal presentation, but were more successful in terms of comprehending content.…”
Section: Literature Reviewmentioning
confidence: 89%
“…Some students delight in visual-spatial learning, others prefer verbal representations, while others learn best by hearing information. As suggested by generative theories of multimedia learning (e.g., Plass, Chun, Mayer, & Leutner, 1998), many prefer a combination, for example hearing and seeing text simultaneously (Montali & Lewandowski, 1996). A substantial body of work by Richard Mayer and his colleagues support the contention that multimedia learning (presenting information in two or more formats such as words and pictures) can be superior to single ways (Mayer, 1997;Mayer et al, 1996;Mayer & Gallini, 1990;Mayer & Moreno, 1998;Mayer & Sims, 1994).…”
Section: Universal Designmentioning
confidence: 99%
“…Although research supports the use of LWR procedures for improving the subsequent oral reading fluency of students with learning and/or behavioral problems (Daly & Martens, 1994;Rose, 1984;Rose & Beattle, 1986), the literature has been less clear about the effectiveness of LWR with respect to reading comprehension. Montali and Lewandowski (1996) compared visual, auditory, and bimodal (LWR) approaches for improving reading comprehension among middle-school students with and without identified reading disabilities. Results of this study favored LWR for most of the students with disabilities.…”
mentioning
confidence: 99%